Novel Cardiac Computed Tomography Methods for the Assessment of Anthracycline Induced Cardiotoxicity - Feher, Attila; Baldassarre, Lauren A.; Sinusas, Albert J. (Frontiers in Cardiovascular Medicine, 2022)
Anthracyclines are among the most frequently utilized anti-cancer therapies; however, their use is frequently associated with off-target cardiotoxic effects. Cardiac computed tomography (CCT) is a validated and rapidly evolving technology for the evaluation of cardiac structures, coronary anatomy and plaque, cardiac function and preprocedural planning. However, with emerging new techniques, CCT is rapidly evolving to offer information beyond the evaluation of cardiac structure and epicardial coronary arteries to provide details on myocardial deformation, extracellular volume, and coronary vasoreactivity. The potential for molecular imaging in CCT is also growing. In the current manuscript we review these emerging computed tomography techniques and their potential role in the evaluation of anthracycline-induced cardiotoxicity.